Political Representation and Human Rights: Identity and Inclusion of Tharu Community (Sambahak: Human Rights Journal, 2024)
Human rights, as the cornerstone of dignity and equality, include the right to identity, which extends beyond individual recognition to affirm a community’s cultural and social heritage. This research explores the critical intersection of political representation and human rights, focusing on the Tharu community’s fight for identity and inclusion in Nepal. Political representation is not merely a matter of numbers but an essential recognition of a community’s voice and aspirations, vital for ensuring equality and protecting cultural heritage. The Tharu community’s ongoing struggle for representation highlights the systemic challenges marginalized groups face in achieving meaningful inclusion within democratic frameworks. This study delves into the historical context, current challenges, and legal frameworks impacting the Tharu community while proposing that true equality demands active acknowledgment of distinct identities in the political and social fabric of Nepal. Addressing these dimensions, the research aims to contribute to the broader discourse on indigenous rights, democracy, and human dignity.